Plumeria obtusa L.: A systematic review of its traditional uses, morphology, phytochemistry and pharmacology - Tanay Bihani; Priyank Tandel; Jyoti Wadekar (Elsevier, 2021)
Background: Plumeria obtusa L. (Apocynaceae) is a deciduous, ornamental, tropical plant grown in premises, parks, gardens, graveyards, because of its attractive and fragrant flowers. The different parts of the plant are used traditionally to treat various diseases like diabetes mellitus, wounds and skin disease, diuretic, purgative, abortion and also used in cosmetics, aromatherapy, necklaces and as offerings. In spite of the many pharmacological properties reported for P. obtusa, there is not a review that studies all the phytochemicals and pharmacological activities and critically analyse all of them. Purpose: The aim of this paper is to provide an overview and critically analyse the reported traditional uses, morphology, phytochemistry, pharmacological activities and toxicological studies of P. obtusa and to identify the remaining gaps and thus supply a basis for further investigations. The review also focuses towards attracting the attention of people and researchers about the wide spread pharmaceutical properties of the plant for its better utilization in the coming future. Methods: Information on P. obtusa was gathered using numerous search engines and publication house such as Pubmed, Springer, Science Direct, Google scholar, Taylor and Francis imprints, NCBI (National centre for Biotechnology Information), Chemspider, Scopus and Wiley, research and review articles from peer- reviewed journals and unpublished data and some other 'grey literature' sources. Results: More than 130 chemical constituents have been isolated from P. obtusa including iridoids, terpenoids, flavonoids, cardiac glycosides, phenolic acids, steroids, fatty acid esters, coumarin, cardenolide, cinnamic acid derivate and volatile oils. The plant possesses a large or wide range of pharmacological activities such as antimicrobial, antiproliferative, antimutagenic, antiinflammatory, antiulcerogenic, algicidal, antioxidant, insecticidal and wound healing. The information related to the toxicity of P. obtusa is limited so far and studies regarding toxicity of plant is needed to be explored. Conclusion: However, many aspects of this plant species have not been studied yet. For example, the activity of the active chemical constituents from P. obtusa has been reported only for one pharmacological activity, while the rest have been proven from the crude extracts, i.e., lack of bioguided isolation strategies and unclear mechanism of action is observed. In addition, the bioavailability, pharmacokinetics and structural activity relationship studies of active ingredient to be isolated need to be studied, which will contribute to the development of a phytopreparation containing P. obtusa extracts. Toxicity studies of the plant are poorly investigated and need to be further explored. Studies are also required on long term in vivo toxicity, toxicity in humans and the clinical efficacy of the plant species.